2014
DOI: 10.1103/physreva.90.033807
|View full text |Cite
|
Sign up to set email alerts
|

Tunable single-photon emission from dipolaritons

Abstract: Abstract. We study a system comprising of a double quantum well embedded in a micropillar optical cavity, where strong coupling between a direct exciton, indirect exciton, and cavity photon is achieved. We show that the resulting hybrid quasiparticles -dipolaritons -can induce strong photon correlations and lead to anti-bunched behaviour of the cavity output field. The origin of the observed single photon emission is attributed to unconventional photon blockade. Moreover, we find that the second-order equal ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 53 publications
2
55
2
Order By: Relevance
“…Because as η → +∞, we have opt → 0 and U opt → 0 from Eqs. (24) and (25), which do not agree with the results given in Eqs. (2) and (3) for the case of ε b = 0.…”
Section: Optimal Antibunching Conditionscontrasting
confidence: 58%
See 2 more Smart Citations
“…Because as η → +∞, we have opt → 0 and U opt → 0 from Eqs. (24) and (25), which do not agree with the results given in Eqs. (2) and (3) for the case of ε b = 0.…”
Section: Optimal Antibunching Conditionscontrasting
confidence: 58%
“…From Eqs. (24) and (25), the optimal conditions for strong antibunching are dependent on the strength ratio between the driving fields η. This implies that we can control the statistic properties of the photons by tuning the strength ratio between the two driving fields.…”
Section: Optimal Antibunching Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the first experimental observation of dipolaritons [24], it was demonstrated that they have distinct response to electric and magnetic fields [29] and stronger interparticle interaction as compared to conventional polaritons [30]. Moreover, they can be used for enhanced electrical control [31,32], facilitate indirect exciton condensate preparation [33], single photon emission [34], and other optoelectronic applications. Particularly, it was predicted that dipolaritons can serve as an efficient ter-ahertz emission source [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The strong photon-photon correlation in this scheme is attributed by the destructive quantum interference between distinct driven-dissipative pathways [20,21]. Based on this mechanism, many different systems are proposed to realize the unconventional photon-blockade [22][23][24][25][26][27][28][29], moreover three oscillatory mode systems have also been considered [30].…”
Section: Introductionmentioning
confidence: 99%